2010
DOI: 10.1186/1756-9966-29-139
|View full text |Cite
|
Sign up to set email alerts
|

Induction of gastric cancer cell adhesion through transforming growth factor-beta1-mediated peritoneal fibrosis

Abstract: BackgroundPeritoneal dissemination is one of the main causes of death in gastric cancer patients. Transforming growth factor-beta1 (TGF-β1), one of the most potent fibrotic stimuli for mesothelial cells, may play a key role in this processing. The purpose of this study is to elucidate the effects of TGF-β1 on regulation of gastric cancer adhesion to mesothelial cells.MethodsPeritoneal tissues and peritoneal wash fluid were obtained for hematoxylin and eosin staining or ELISA to measure fibrosis and TGF-β1 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…TGF-β1 has been established to promote the expression of extracellular matrix (ECM) factors, including collagen, through Smad3 and the conversion of renal tubular epithelial cells into fibroblasts in the kidney via Smad2 (24). Regarding gastric cancer, TGF-β1 levels detected using an ELISA with peritoneal wash fluid samples are associated with peritoneal dissemination and depth of invasion (18). Furthermore, TGF-β1 induces the EMT of HPMCs in vitro and in vivo (25).…”
Section: Adhesion To the Peritoneummentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β1 has been established to promote the expression of extracellular matrix (ECM) factors, including collagen, through Smad3 and the conversion of renal tubular epithelial cells into fibroblasts in the kidney via Smad2 (24). Regarding gastric cancer, TGF-β1 levels detected using an ELISA with peritoneal wash fluid samples are associated with peritoneal dissemination and depth of invasion (18). Furthermore, TGF-β1 induces the EMT of HPMCs in vitro and in vivo (25).…”
Section: Adhesion To the Peritoneummentioning
confidence: 99%
“…Subsequent previous studies have further demonstrated that TGF-β1 increases the expression of collagen I in rat peritoneal mesothelial cells via the c-Jun N-terminal kinase (JNK)/Smad3 signalling pathway, and of collagen III and fibronectin of HPMCs via Smad2 (26,27). Consequently, mesothelial cells stimulated by TGF-β1 promote peritoneal fibrosis via upregulating the expression of ECM proteins, including collagen I, collagen III and fibronectin (18). Cancer cells may anchor to the ECM via adhesion molecules; therefore peritoneal fibrosis mediated by TGF-β1 provides an effective 'soil' for dissemination.…”
Section: Adhesion To the Peritoneummentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the interaction of GC cells with the ECM appears to be of considerable importance in peritoneal metastasis as cancer cells that exfoliated into the abdominal cavity were found to attach initially to the mesothelial lining, followed by their invasion through the intercellular gaps of mesothelial cells (31). This study indicated that the adhesion of integrin α1-positive GC cells to the ECM is a critical process in peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 82%
“…It can also regulate multiple cellular functions, including both inhibition and stimulation of proliferation, apoptosis and differentiation. Our previous study demonstrated that the TGF-β1 levels in peritoneal lavage fluid are significantly correlated with peritoneal metastasis and TNM stages of gastric cancer (9,10). In addition, TGF-β1 stimulates both the invasion and adhesion of gastric cancer cells to the peritoneum, thus resulting in an increase of the potential for peritoneal dissemination (11).…”
Section: Introductionmentioning
confidence: 99%